Development of Android-Based Gamification Learning Media for Multiplication Material for Grade III Elementary School Students - Suprayekti; Kunto Imbar; Della Nuari; Ariani, Diana; Widyaningrum, Retno; Kustandi, Cecep (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
The lack of practice questions given by the teacher resulted in students having difficulties in operating multiplication. This study aims to produce an android-based gamification application as a medium to support the learning process in operating multiplication material for third grade elementary school students. This development research uses the Rapid Prototyping model. The subjects involved in this study consisted of 2 material experts, 1 instructional design expert, 1 media expert, 3 students for individual trials, 9 students for small group trials, and 15 students for field trials. Data collection methods used are unstructured interviews and questionnaires. The gamification development process is carried out through 5 stages, namely (a) needs analysis and content analysis, (b) determining objectives, (c) building prototypes, (d) utilizing prototypes, (e) system installation and maintenance. The results of the expert review showed improvement, the results of individual trials and small group trials for all aspects received a positive response but there were 3 suggestions for improvement in the small group test, and the results of the field trial of 15 students had achieved a score above the minimum completeness criteria. Based on the results of this analysis, it can be concluded that Android-based gamification media can be used as enrichment for independent learning for third grade elementary school students.